The Role of Mobile Phones in the Transmission of Bacteria and Fungi Associated with Hospital-acquired infections in Erbil City - Sheylan S. Abdullah (Polytechnic Journal)
Background and objectives: The widespread use of cellular devices, particularly by hospital staff, contributes to the spread of pathogenic organisms. The study was conducted to determine the microbial contamination of cellular mobile devices in health care workers (HCW) and to compare it with mobile phones of non-HCW’s. Materials and Methods: Mobile phones of 90 HCW’s were screened for microbial contamination and it is compared with mobile phones of 90 non-HCW’s. A sterile moistened swab sample was taken and rotated over the surfaces [both sides] of the cell phones and inoculated in nutrient broth at 37°C for 24 hours, followed by sub-culturing on agar such as: MacConkey agar, Mannitol salt agar, blood base agar and Sabouraud dextrose agar. The isolated microorganism was identified by using standard microbiological techniques. Results: The study revealed microbial contamination in case of 90 mobile phones of HCW’s and 90 mobile phones from non-HCW’s. Commonest organism isolated was Coagulase negative Staphylococci in HCW’s groups. 81 microbe isolates (61.83%) from HCW’s were significant nosocomial pathogens whereas 68 isolates (59.13%) from non-HCW were pathogenic; Staphylococcus aureus being the most frequent isolate from non-HCW groups. examined samples showed that (100%) were contaminated with one or more organisms. Five different bacterial species were found to be present. (46.67%) Coagulase Negative Staphylococci, (43.33 %) for each Staphylococcus aureus and Streptococcus spp., (4.44 %) E. coli, (3.33%) Pseudomonas spp. and fungal isolates include (3.33%) Aspergillus spp. and Candida spp. (1.11%). Medical lab samples showed high rates (53.33%) of mixed growth compared with (23.33%) and (20%) from doctor and nurses respectively. In addition, samples taken from females showed a higher contamination rate of single growth (75.56%) than samples taken from males (60%). Conclusions: According to the study, the use of mobile devices by HCWs serves as a reservoir for microorganisms. In order to stop the spread of infectious germs, these should be frequently disinfected as well as using good hand hygiene techniques. Additionally screening of mobile device for the nosocomial pathogens and restricting their use in sensitive areas of hospital is also advisable.